A practitioner-friendly approach to quantifying the hydrologic benefits of city-scale distributed green stormwater infrastructure - Matthew L. Chambers; Felix L. Santiago-Collazo; Roderick W. Lammers; Brian P. Bledsoe (Journal of Environmental Management, 2026)

From wastewater to sludge: The role of microplastics in shaping anaerobic digestion performance and antibiotic resistance gene dynamics - Yasna Mortezaei; Mohamed S. Gaballah; Goksel N. Demirer; Roderick W. Lammers; Maggie R. Williams (Journal of Hazardous Materials, 2025)

Assessing the factors influencing constructed wetland performance for mitigating agricultural nutrient runoff in the U.S. - Mohamed S. Gaballah; Roderick W. Lammers (Journal of Water Process Engineering, 2025)

Free water surface constructed wetlands: review of pollutant removal performance and modeling approaches - Mohamed S. Gaballah; Hooshyar Yousefyani; Mohammadjavad Karami; Roderick W. Lammers (Environmental Science and Pollution Research, 2024)

The role of warm, dry summers and variation in snowpack on phytoplankton dynamics in mountain lakes - Isabella A. Oleksy; Whitney S. Beck; Roderick W. Lammers; Cara E. Steger; Codie Wilson; Kyle Christianson; Kim Vincent; Gunnar Johnson; Pieter T. J. Johnson; J. S. Baron (Ecology, 2020)
Climate change is altering biogeochemical, metabolic, and ecological functions in lakes across the globe. Historically, mountain lakes in temperate regions have been unproductive because of brief ice‐free seasons, a snowmelt‐driven hydrograph, cold temperatures, and steep topography with low vegetation and soil cover. We tested the relative importance of winter and summer weather, watershed characteristics, and water chemistry as drivers of phytoplankton dynamics. Using boosted regression tree models for 28 mountain lakes in Colorado, we examined regional, intraseasonal, and interannual drivers of variability in chlorophyll a as a proxy for lake phytoplankton. Phytoplankton biomass was inversely related to the maximum snow water equivalent (SWE) of the previous winter, as others have found. However, even in years with average SWE, summer precipitation extremes and warming enhanced phytoplankton biomass. Peak seasonal phytoplankton biomass coincided with the warmest water temperatures and lowest nitrogen‐to‐phosphorus ratios. Although links between snowpack, lake temperature, nutrients, and organic‐matter dynamics are increasingly recognized as critical drivers of change in high‐elevation lakes, our results highlight the additional influence of summer conditions on lake productivity in response to ongoing changes in climate. Continued changes in the timing, type, and magnitude of precipitation in combination with other global‐change drivers (e.g., nutrient deposition) will affect production in mountain lakes, potentially shifting these historically oligotrophic lakes toward new ecosystem states. Ultimately, a deeper understanding of these drivers and pattern at multiple scales will allow us to anticipate ecological consequences of global change better.

What role does stream restoration play in nutrient management? - Roderick W. Lammers; Brian P. Bledsoe (Critical Reviews in Environmental Science and Technology, 2017)